2022
DOI: 10.1039/d2dt00074a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel -doped iron oxide nanoparticle-conjugated porphyrin interface (porphyrin/Fe2O3@Ni) for the non-enzymatic detection of dopamine from lacrimal fluid

Abstract: Exploring a robust, extremely sensitive, cost-effective and reliable assay platform for precise analysis of dopamine (DA) has become a big challenge predominantly at clinical level. To participate in this quest,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The value of α was premeditated from eqn (3) and found to be 0.03. 45,46 whereas R represents the general gas constant, while T , α , F and n correspond to the absolute temperature, electron transfer coefficient, Faraday constant, and number of electrons transferred. Similarly, the number of electrons transferred at the surface of La@CuO-DMT was found to be 2.30, suggesting the two-electron and two-proton-coupled mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The value of α was premeditated from eqn (3) and found to be 0.03. 45,46 whereas R represents the general gas constant, while T , α , F and n correspond to the absolute temperature, electron transfer coefficient, Faraday constant, and number of electrons transferred. Similarly, the number of electrons transferred at the surface of La@CuO-DMT was found to be 2.30, suggesting the two-electron and two-proton-coupled mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the diverse chemical and physical properties combined with other capabilities/characteristics turn nanocomposite materials well distinguished from their bulk counterparts. 10,62,63 Therefore, considering these supreme properties and features, we concluded that making composite materials substantially impacted the electrochemical charge storage performance of the active electrode materials. As discussed, the layered structure of the FeSe 2 initiates various oxidation states, e.g.…”
Section: Charge Storage Mechanism In Fese2 Systemsmentioning
confidence: 96%
“…[295,296] They influence mood, heart rate, and muscle moment and have been associated with many physiological moments. [297,298] Rui et al [299] prepared Ti 3 C 2 by layer liquid exfoliation to modify the gate electrode. Further, the GCE was fabricated with Pt/Ti 3 C 2 and used as a gate that was assembled with graphene monolayer to develop a complete transistor (Figure 9A).…”
Section: Neurotransmitters Biosensingmentioning
confidence: 99%
“…[ 295,296 ] They influence mood, heart rate, and muscle moment and have been associated with many physiological moments. [ 297,298 ] Rui et al. [ 299 ] prepared Ti 3 C 2 by layer liquid exfoliation to modify the gate electrode.…”
Section: Mxene‐based Biosensorsmentioning
confidence: 99%